The influence of shari’ah-compliant e-commerce models on consumer trust - I.A, Muhammad Kholifatul; Yunizar; Harsanto, Budi (2015)
This study is aimed at finding out the real picture of Shari’ah-compliant E-commerce Model and consumer trust in e commerce today, analyzing its drawbacks, and finding out how they influence each other.Shari'ah-compliant E-commerce model is a model that describes how e-commerce should run in accordance with the provisions of the Shari’ah. Broadly speaking, e-commerce in the perspective of Shari’ah must comply with some rules, namely: 1. the form of the offer and transaction agreement, 2. the transacting parties (buyers and sellers), 3. Objects and prices in the transaction, and 4. Free from major prohibitions in transactions, namely (i) interest (riba), (i) gambling (maysir), (iii) uncertainty (gharar), (iv) coercion (ikrah) and (v) the prohibition (haram in nature).The sample in this study is Indonesian citizen who are consumers of e commerce.The number of sample used in this study is 90 respondents.This research uses descriptive and statistical methods with multiple linear regression model.This model is considered relevant and good to be studied in order to enlighten how e commerce is currently in the perspective of Islam.